Kelimpahan Tungau Predator pada Tanaman Melati Gambir (Jasminum officinale) di Desa Cipawon, Bukateja, Purbalingga, Jawa Tengah - Ika Rakhmayani; Bambang Heru Budianto; Trisnowati Budi Ambarningrum (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
The Gambier Jasmine plant (Jasminum officinale) is located in Bukateja District, Cipawon Village, Purbalingga, Central Java is a commodity with high economic value, its use a tea fragrance, cosmetics, perfumes dan others. One of the cause of decreased productivity of Gambier Jasmine is ude to the presence of pets, namely mites. The pest mite population is controlled by predatory mites. Therefore, this study aimed to determne the types of predatory mites and determine the abundance of predatory mites in Gambier Jasmine (J. officinale) in Cipawon Village, Purbalingga, Central Java. This research used survey method with purposive sampling technique. There are nine sampling points, eight pointa on the outer edge and one point in the middle of plantation. Each sampling is represented by three trees. The sample in the form of Gambier Jasmine Leaves came form the lowest ten leaf stalks in one tree at each sampling point. The number of leaf samples obtained was 270 leaf samples. Each sampling point was taken three times with one week intervals. The variable observed include the number of individuals and the number of species of predatory mites on the Gambier Jasmine (J. officinale) and the parameters calculated were leaf area, leaf sitting angle, length and density of trichomes, temperature, humidity, asa well as rainfall. The data obtained were analyzed by analysis of variance (ANOVA) with an error rate of 20%. The result of the identification of predatory mites on the Gambier Jasmine plant were obtained by two species, namely Amblyseius largoensis and Phytoseius amba. A. largoensis as many as 76 individuals with an abundance percentage of 61,8% and P. amba as many as 47 individuals with an abundance percentage of 38,2%. The abundance of predatory mites A. largoensis and P. amba is classified as moderate because predators are easy to find, every three leaves there is one predator. Key words: abundance., Cipawon., Gambier Jasmine., predatory mites.